Essential Oil Composition and Antibacterial Activity of Tanacetum argenteum (Lam.) Willd. ssp argenteum and T. densum (Lab.) Schultz Bip. ssp amani Heywood from Turkey - Polatoglu, Kaan; Demirci, Fatih; Demirci, Betuel; Goren, Nezhun; Baser, Kemal Huesnue Can (JAPAN OIL CHEMISTS SOC, 2010)
Water-distilled essential oils from aerial parts of Tanacetum argenteum ssp. argenteum and T densum ssp. amani from Turkey were analyzed by GC and GC/MS. The essential oil of T. argenteum ssp. argenteum was characterized with alpha-pinene 36.7%, beta-pinene 27.5% and 1,8-cineole 9.8%. T. densum ssp. amani was characterized with beta-pinene 27.2%, 1,8-cineole 13.1%, alpha-pinene 9.7% and p-cymene 8.9 A. Antibacterial activity of the oils were evaluated for five Gram-positive and five Gram-negative bacteria by using a broth microdilution assay. The highest inhibitory activity was observed against Bacillus cereus for E argenteum ssp. argenteum oil (125 mu g/mL) when compared with positive control chloramphenicol it showed the same inhibition potency. However, the same oil showed lower inhibitory activity against B. subtilis when compared. The oil of T densum ssp. amani did not show significant activity against the tested microorganisms. DPPH radical scavenging activity of the T argenteum ssp. argenteum oil was investigated for 15 and 10 mg/mL concentrations. However, the oil did not show significant activity when compared to positive control a-tocopherol. Both oils showed toxicity to Vibrio fischeri in the TLC-bioluminescence assay.
Keywords: Tanacetum argenteum ssp argenteum; T. densum ssp amani; Asteraceae; essential oils; alpha-pinene; beta-pinene; 1,8-cineole; DPPH radical scavenging; antibacterial activity; Vibrio fischeri toxicity; RADICAL-SCAVENGING ACTIVITY; SESQUITERPENE LACTONES; ENANTIOMERIC DISTRIBUTION; SUBSP FLABELLIFOLIUM; VAR.-CHILIOPHYLLUM; BACILLUS-CEREUS; SIVASICUM; GUAIANOLIDE; GRIERSON; CANUM; Chemistry; Food Science & Technology